Formulasi Dan Evaluasi Sediaan Gel Tabir Surya Dari Serbuk Cangkang Telur Ayam Ras (Gallus Gallus) Dengan Variasi Basis Gel Carbopol 940 Dan HPMC - Sukmawati; Yuliani, Elsa (Jurnal Medika Farmaka, 2023)
Introduction: Egg shells of purebred chickens (Gallus gallus) are one of the wastes that contain active calcium compounds, especially calcium carbonate compounds which have a physical blocker mechanism of action in sunscreens by reflecting UV radiation to form an opaque layer on the surface of the skin. Method: Method: This research method was experimental in the laboratory by making 4 sunscreen gel formulas from purebred chicken eggshell powder with a concentration of 15% consisting of F0 without base, F1 Carbopol 940 0.5% and 1% HPMC, F2 Carbopol 940 0.75% and HPMC 0.75%, F3 Carbopol 940 1% and HPMC 0.5%. Evaluation of sunscreen gel preparations included the stability of the preparation in the organoleptic test, homogeneity test, pH test, viscosity test, spreadability test, adhesion test and microbial contamination test. Result: All sunscreen gel preparation formulas show a brownish-white color, thick texture, characteristic odor, and are homogeneous. The pH value is 7. The adhesion value is > 1 second. Spread power value 5-7 cm. Viscosity values ​​in the range of 2000-50,000 cps. The results of the stability test at room temperature, cold temperature and hot temperature remained stable during 28 days of storage, there were no changes from organoleptic observations, homogeneity and pH, but there was a decrease in the viscosity value at room temperature and hot temperature storage and a change in the color of the preparation at hot temperatures. And the results of the microbial contamination test with the Total Plate Count test of the 4 formulas met the requirements of <102 colonies/mL. Conclusion. Based on this, it can be concluded that purebred chicken egg shell powder (Gallus gallus) can be formulated into a facial serum cosmetic preparation and meets the quality requirements according to SNI.